Primary Students’ Mastery on Minimum Learning Competencies in Cognitive Areas based on Gender - Gure, Gobind Singh (THE PRIMARY TEACHER, 2016)
The purpose of the study is to find out the mastery of primary school students on minimum level of learning competencies in cognitive areas in relation with their gender. The primary data were collected by administering three standardised achievement questionnaires of NCERT (Hindi, mathematics and environment studies) on 600 primary and elementary school students from 30 schools (20 from Haryana and 10 from Chandigarh). The data were analysed with the help of descriptive and non-parametric statistics. The study revealed a significant difference existed between boys and girls as regards to mastery on minimum level of learning competencies in cognitive areas. Girls showed a higher level of minimum level of learning in Hindi than boys. It was found that both boys and girls did not notice any statistical difference in mathematics and environmental studies. Overall, only 21, 10 and 8 per cent students were found to have achieved mastery on minimum level of learning competencies in Hindi, mathematics and environmental science, respectively. On the basis of the findings, it is suggested that teachers, educational institutions and administration take care about the evaluation of learning competencies and feedback. Besides, constructive approach must be adopted in teaching at the primary level for ensuring better performance by students.